Design and experimental research on ultrasonic levitated spherical rotor gyroscope - Junshan Wang; Lei Jian; Chao Chen; Lusheng Qiang (AIP Advances, 2020)
This study proposes a spherical rotor gyroscope based on the near-field acoustic levitation (NFAL) principle, which utilizes high-frequency vibration to levitate objects at a short distance near the driving surface. The ultrasonic suspended gyroscope consists of a piezoelectrically excited stator and a spherical rotor. The stator was excited to generate ultrasonic vibration under the action of the inverse piezoelectric effect, provide non-contact support for the spherical rotor, and drive it to rotate with the traveling wave vibration. When the spherical rotor obtained sufficient angular momentum, the driving voltages were changed to induce the standing wave vibration and thus provide a stable levitation force field for the rotor. At this stage, the rotor was only subjected to the effects of gravity and levitation force and the spherical rotor rotated at a high speed to obtain gyroscopic inertia. Herein, the finite element model of the stator was established for dynamic analysis, and an acoustic–structure coupling model was established to analyze the non-contact supporting force of the gyroscope. The prototype was manufactured, and the stator was tested for vibration, and test platforms for levitation height, rotation speed, and gyroscopic inertia of the non-contact ultrasonic levitated spherical rotor gyroscope were built. The stator vibration performance was consistent with the simulation analysis result. The levitation height could be as high as tens of microns at the operating frequency. The rotation speed could reach 5600 r/min, and the gyroscopic inertia was verified. Therefore, the feasibility of NFAL for a levitated gyroscope was verified.